Resistance of Francisella Novicida to Fosmidomycin Associated with Mutations in the Glycerol-3-Phosphate Transporter - Mackie, Ryan S.; McKenney, Elizabeth S.; van Hoek, Monique L. (Frontiers in Microbiology, 2012)
The methylerythritol phosphate (MEP) pathway is essential in most prokaryotes and some lower eukaryotes but absent from human cells, and is a validated target for antimicrobial drug development. The formation of MEP is catalyzed by 1-deoxy-d-xylulose 5-phosphate reductoisomerase (DXR). MEP pathway genes have been identified in many category A and B biothreat agents, including Francisella tularensis, which causes the zoonosis tularemia. Fosmidomycin (Fos) inhibits purified Francisella DXR. This compound also inhibits the growth of F. tularensis NIH B38, F. novicida and F. tularensis subsp. holarctica LVS bacteria. Related compounds such as FR900098 and the lipophilic prodrug of FR900098 (compound 1) have been developed to improve the bioavailability of these DXR inhibitors. In performing disk-inhibition assays with these compounds, we observed breakthrough colonies of F. novicida in the presence of Fos, suggesting spontaneous development of Fos resistance (FosR). FosR bacteria had decreased sensitivity to both Fos and FR900098. The two most likely targets for the development of mutants would be the DXR enzyme itself or the glycerol-3-phosphate transporter (GlpT) that allows entry of Fos into the bacteria. Sensitivity of FosRF. novicida bacteria to compound 1 was not abated suggesting that spontaneous resistance is not due to mutation of DXR. We thus predicted that the glpT transporter may be mutated leading to this resistant phenotype. Supporting this, transposon insertion mutants at the glpT locus were also found to be resistant to Fos. DNA sequencing of four different spontaneous FosR colonies demonstrated a variety of deletions in the glpT coding region. The overall frequency of FosR mutations in F. novicida was determined to be 6.3 × 10−8. Thus we conclude that one mechanism of resistance of F. novicida to Fos is caused by mutations in GlpT. This is the first description of spontaneous mutations in Francisella leading to FosR.